2017
DOI: 10.1515/aiht-2017-68-2974
|View full text |Cite
|
Sign up to set email alerts
|

Salivary sCD14 as a potential biomarker of dental caries activity in adults

Abstract: CD14 is a co-receptor involved in the recognition of Gram-negative and Gram-positive bacteria, the latter known to cause dental caries. The aim of this study was to determine whether soluble CD14 (sCD14) in saliva was associated with caries activity and the collection method from the saliva. The study included 55 participants aged 20 to 40 years, 30 with dental caries and 25 caries-free controls. We collected 110 saliva samples in total, 55 of resting saliva and 55 of mechanically stimulated saliva. Median lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…The sCD14 level was high in group with caries involving pulp along with apical periodontitis when compared to control group. This result was in corroboration with the previous study [25]. The reason for difference in the sCD14 level is because of the innate immune response by recognition of lipopolysaccharide (LPS), endotoxins and peptidoglycan [26].…”
Section: Discussionsupporting
confidence: 92%
“…The sCD14 level was high in group with caries involving pulp along with apical periodontitis when compared to control group. This result was in corroboration with the previous study [25]. The reason for difference in the sCD14 level is because of the innate immune response by recognition of lipopolysaccharide (LPS), endotoxins and peptidoglycan [26].…”
Section: Discussionsupporting
confidence: 92%
“…At the immune assay analysis, saliva sCD14 content resulted significantly lower in patients with decayed teeth than in healthy subjects. This data seems to confirm the relationship between the investigated protein and the development of dental caries and are in accordance with the literature [12][13][14][15]. Authors detected the experimental protein by ELISA test and Western blot and reported lower levels, or even the complete absence [15], of sCD14 in patients with at least one carious lesion [13][14][15] than in caries free subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Infact, sCD14 amount resulted not indicative of the presence/absence of dental caries. Furthermore, even if an inverse correlation was found between the protein level and the number of decayed teeth in accordance to previous studies [12][13][14][15], the high interindividual variability that was found also in literature, does not allow to establish a range standard for all subjects of correspondence between sCD14 amount and degree of this dental disease. However, it may be possible to combine it with other markers/lifestyle risk factors that are known to be associated with carious lesions and construct a multivariate probability profile that is more capable of discriminating between healthy and diseased subjects.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The investigation of stress biomarkers has achieved recognition because saliva sample collection is standardised, non-invasive and easy to manage. Studies have shown that saliva can be used in chair-side tests for many oral and systemic diseases 8 . Saliva is useful because of its many analytes that are affected by a variety of conditions and physiological and pathological stressors 9 .…”
Section: Introductionmentioning
confidence: 99%